Udział kardynała Karola Wojtyły w pracach Rady Świeckich - Dyduch, Jan (Prawo Kanoniczne, 1996)
The Post Conciliar renewal of the Church tended to engage the laity in its apostolic activity. It required global organization and co-ordunation. This task was assumed by the Council for the Laity, established by Pope Paul VI on January 6, 1967. Cardinal Karol Wojtyła was its consultant for almost ten years. While taking part in the Concil’s work, he carefully watched that its action would be based on the teaching and instructions of Vatican II, extendig its interest to the entire lay apostolate. He attached great importance to the question that the Council for the Laity should deal, not only with Catholic organizations, but also with other forms of lay apostolate activities. It was his desire that the Council would be composed of the laity of the universal Church and would be its representative. While elaborating the method of procedure, he stressed the need for Council’s cooperation, not only with Catholic organizations, but also with National Conferences of Catolic Bishops, especially with their Catholic Laity Committees. Cardinal K. Wojtyła himself, being a chairman of the Lay Apostolate Committee of the Episcopate of Poland, took utmost care about keeping intense and fruitful contacts with the Council for the Laity.